Perinatal Outcomes of Fetuses with Early Growth Restriction, Late Growth Restriction, Small for Gestational Age, and Adequate for Gestational Age - Quênya Antunes Silveira Inácio; Edward Araujo Júnior; Luciano Marcondes Machado Nardozza; Caetano Galvão Petrini; Victor Paranaíba Campos; Alberto Borges Peixoto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To evaluate the association between early-onset fetal growth restriction (FGR), late-onset FGR, small for gestational age (SGA) and adequate for gestational age (AGA) fetuses and adverse perinatal outcomes. Methods This was a retrospective longitudinal study in which 4 groups were evaluated: 1 - early-onset FGR (before 32 weeks) (n=20), 2 - late-onset FGR (at or after 32 weeks) (n=113), 3 - SGA (n=59), 4 - AGA (n=476). The Kaplan-Meier curve was used to compare the time from the diagnosis of FGR to birth. Logistic regression was used to determine the best predictors of adverse perinatal outcomes in fetuses with FGR and SGA. Results A longer timebetween the diagnosis and birthwas observed forAGAthan for late FGR fetuses (p<0.001). The model including the type of FGR and the gestational age at birth was significant in predicting the risk of hospitalization in the neonatal intensive care unit (ICU) (p<0.001). The model including only the type of FGR predicted the risk of needing neonatal resuscitation (p<0.001), of respiratory distress (p<0.001), and of birth at<32, 34, and 37 weeks of gestation, respectively (p<0.001). Conclusion Fetal growth restriction and SGA were associated with adverse perinatal outcomes. The type of FGR at the moment of diagnosis was an independent variable to predict respiratory distress and the need for neonatal resuscitation. The model including both the type of FGR and the gestational age at birth predicted the risk of needing neonatal ICU hospitalization.